Implementasi Pembelajaran Kooperatif Berbasis Kasus Untuk Meningkatkan Efektivitas Pembelajaran Kecerdasan Buatan - Haryanto Haryanto; M Khairudin (Faculty of Engineering, Universitas Negeri Yogyakarta, 2014)
The objectives of this study were 1) to determine the effectiveness of Case-Based Cooperative Learning in the context of Student-Centered Learning 2) to improve the students’ cognitive abilities in order to increase the learning achievement. This study was conducted in the Department of Electrical Engineering Education, Faculty of Engineering, Yogyakarta State University. The learning method was applied in the subject of Artificial Intelligence, the Study Program of Electrical Engineering and Mechatronics Education for the students of 2010 academic year. The data collection techniques were observation, tests and questionnaires. The data was analysed using quantitative descriptive and regression analysis. The results showed 1) there is significant effect of the Case-Based Learning on the students’ cognitive abilities 2) there is significant effect of Cooperative Learning on the students’ cognitive abilities 3) there is significant effect of Student-Centered Learning on the students’ cognitive abilities 4) there is 47% significant effect of Case Based Learning, Cooperative Learning and Student-Centered Learning on the students’ cognitive abilities.